Aplicação de extratos da casca de guabiroba (Campomanesia xanthocarpa) como agente antioxidante em patês de tilápia - Pires, Cintia Lurdes da Silva (2020)
Guabiroba (Campomanesia xanthocarpa) is a fruit native to Brazil rich in phenolic compounds, vitamin C, and has antioxidant activity, however it is still little used. Fish products are susceptible to lipid oxidation due to the characteristics of the raw material, so the use of natural ingredients is an alternative to reduce this issue. The objective of this work was to characterize and apply extracts of guabiroba bark as an antioxidant agent in tilapia pâtés. The extracts of guabiroba bark obtained by decoction (ED) and hydroalcoholic (EH) were characterized by the analysis of sequestration of the DPPH radical, ability to reduce ferric ion, total phenolic compounds, vitamin C, titratable acidity and identification of compounds by chromatography (GC-MS and HPLC). Four formulations of tilapia pâtés were elaborated, being: control (without addition of extract and additive) (C), with addition of the extract obtained by decoction (D), with addition of hydroalcoholic extract (H) and with addition of the synthetic additive BHT (BHT). pH, substances reactive to thiobarbituric acid (TBARS), instrumental color, microbiological analysis and sensory analysis were evaluated during the refrigerated storage of the pâtés for 90 days. The extracts showed high levels of vitamin C, phenolic compounds and good antioxidant capacity by the methods used. The extracts were able to reduce lipid oxidation in the pâtés during refrigerated storage, compared to C and BHT formulations. pH remained neutral and within acceptable limits for fish products. For the titratable acidity, there was no difference between the initial and final times for the four formulations. Regarding color, the parameters L* and Croma showed differences only between formulations, but not during storage times. For the Hue angle, the pate with extract obtained by decoction showed the lowest value. The products maintained their microbiological quality at the end of the study, according to criteria established by Brazilian legislation. The pâtés with added extracts showed the lowest averages in the sensory analysis, but the sensory attributes remained with good quality at the beginning and at the end of the study, according to the scale used. Thus, guabiroba bark extracts have the potential to be used in tilapia pâtés as an antioxidant and an alternative to synthetic antioxidants used in fish products.